Dental treatment needs among patients undergoing screening at a university-based dental institution in Kuantan, Pahang, Malaysia - Ismail, Azlini; Abllah, Zurainie; Muhammad Radhi, Nur Aishah; Musa, Syazalina; Abdul Halim, Mohd Firdaus Akbar (Kulliyyah of Dentistry, International Islamic University Malaysia, 2020)
University-based dental institution in Malaysia receives large number of dental visits, however, dental treatment needs among patients attending this kind of institution is not usually reported. This study aimed to identify the trend of dental treatment needs in a university-based dental institution in Kuantan, Pahang situated in the East Coast region of Peninsular Malaysia. This cross-sectional study utilized secondary data, obtained from list of patients who underwent for screening at Outpatient Clinic, Kulliyyah of Dentistry, International Islamic University Malaysia from 1st January to 31st December 2016. Patient’s age, gender, residential area and dental treatment needs were retrieved from the list. All patients were included except those with incomplete data, with old Malaysian identification card or foreign passport or those assigned to receive Orthodontic treatment. Descriptive statistics and Pearson’s Chi Square test was run using SPSS® Version 20 software. Conservative care (22.7 %) was the major treatment need among 2,627 patients included in this study. Teenage and adult patients mostly required conservative care while the elder- aged patients have major need for prosthodontics. Females outnumbered males in requiring all types of dental treatment, except for conservative care which was pre-dominantly required by males. Patients residing non-urban area majorly required all types of dental treatment except for endodontics and conservative care which were more frequently necessitated by patients from urban area. Conservative care was the major dental treatment need. The type of dental treatment needs has significant association with patient’s age, gender and residential area.